Term premiums in bond returns - Fama, Eugene F (Journal of Financial Economics, 1984)
This paper examines expected returns on U.S. Treasury bills and on U.S. Government bond portfolios. Expected bill returns are estimated from forward rates and from sample average returns. Both estimation methods indicate that expected returns on bills tend to peak at eight or nine months and never increase monotonically out to twelve months. Reliable inferences are limited to Treasury bills and thus to maturities up to a year. The variability of longer-term bond returns preempts precise conclusions about their expected returns.